Analisis Visual Media Promosi Poin Festival 2022 Dalam Meningkatkan Loyalitas Konsumen: (Studi Kasus: Program Key Visual Telkomsel Poin Poin Festival periode November-Desember 2022) - Tri Hudaya, Dedy (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2023)
Telkomsel Poin is the retention Telkomsel subscriber for all having Poin from charging pulse and data package prepaid customer and Halo. Telkomsel make various whether they are monthly loyalty program, weekly and thematic. In the meantime Telkomsel Poin make special program Poin Festival 2022 after govermen issued a policy about the latest PPKM held in ofÏ”line in Summarecon Mal Serpong and other digital campaign. Poin Festival 2022 campaign poin covering several important way as lucky draw, cuan hepi, dan mendadak Hepi. Concept of creative implementation in combined with the modern trend classic festival which are reÏ”lected in the use of composition color, texture and attractive form.The vibrant color using color and texture to the shape of objects.Textures that are used as gradation by various forms as oval, box, of images and information as a barrier between messages. Media campaign assets such as through digital media channel, the digital media placement Google. The goal to cover all segment by using the method story, how, audience, reach and excellence.